From MASH to HCC: the role of Gas6/TAM receptors - Apostolo, Daria; Ferreira, Luciana L.; Vincenzi, Federica; Vercellino, Nicole; Minisini, Rosalba; Latini, Federico; Ferrari, Barbara; Burlone, Michela E.; Pirisi, Mario; Bellan, Mattia (Frontiers in Immunology, 2024)
Metabolic dysfunction-associated steatohepatitis (MASH) is the replacement term for what used to be called nonalcoholic steatohepatitis (NASH). It is characterized by inflammation and injury of the liver in the presence of cardiometabolic risk factors and may eventually result in the development of hepatocellular carcinoma (HCC), the most common form of primary liver cancer. Several pathogenic mechanisms are involved in the transition from MASH to HCC, encompassing metabolic injury, inflammation, immune dysregulation and fibrosis. In this context, Gas6 (Growth Arrest-Specific 6) and TAM (Tyro3, Axl, and MerTK) receptors may play important roles. The Gas6/TAM family is involved in the modulation of inflammation, lipid metabolism, fibrosis, tumor progression and metastasis, processes which play an important role in the pathophysiology of acute and chronic liver diseases. In this review, we discuss MASH-associated HCC and the potential involvement of the Gas6/TAM system in disease development and progression. In addition, since therapeutic strategies for MASH and HCC are limited, we also speculate regarding possible future treatments involving the targeting of Gas6 or TAM receptors.